3D TUDE MOVIE SERIES “HANDBAN KEBERUNTUNGAN” - I Kadek Agus Sutrisna; Padma Nyoman Crisnapati; I Made Gede Sunarya; Made Windu Antara Kesiman (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
3D animation movie titled "Handban Keberuntungan" is one of the animated film that contains educational and moral messages to spectators, where the film teache that people appreciate more effort than simply believe in the things that bring good luck, because luck will come if we want to try. The research method or design of 3-D animated film "Handban Keberuntungan" is using the Block diagram method. Where in the Block Diagram describes the steps of making 3-D animated film "Handban keberuntungan" from start to finish. In the block diagram step is divided into three (3) main phases: 1) PreProduction (Idea Story, Scriptwriting, Set the Output Format, Character Design, Image Design Support and Making the Storyboard), 2) Production (Modelling, Texturing, Rigging, Skinning, Acting / Animation, Lighting, and Rendering), 3) Post Production (Recording and Merger Process). The final result is 3-D animation film in DVD format. With hope this film can be used as media for learning both from young people and children. Also, it can introduce the technology of 3-D animated film so that can provide new knowledge for the spectators.